2019
DOI: 10.1177/1362168819829017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of collaborative writing in an EFL secondary setting

Abstract: Collaborative writing (CW) has been proven advantageous to enhance the second and foreign language skills of university students. However, little research to date has explored whether CW practices are fruitful for secondary school learners in foreign language (FL) contexts, a population characterized by low language proficiency levels, and few opportunities to engage with the FL. The present classroom-based study examines CW in this setting and aims to determine whether CW fosters language opportunities, opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 54 publications
5
39
0
1
Order By: Relevance
“…Therefore, the second hypothesis was accepted. This result agrees with the results of some studies which found that CBCW yielded the production of better quality texts (e.g., Abrams, 2019;Al-Shumaimeri, 2011;Arslan & Sahin-Kizil, 2010;Bailey & Judd, 2018;Beltrán, 2010;Daskalogiannaki, 2012;Dobao, 2012;Doult & Walker, 2014;Kessler & Bikowski, 2010;Mak & Coniam, 2008;McDonough & García-Fuentes, 2015;Mills & Exley, 2014;Myers, 2014;Shukor & Noordin, 2014;Strobl, 2014;Togatorop, 2015;Villarreal & Gil-Sarratea, 2019;Wichadee, 2011;Yeh, 2014;.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, the second hypothesis was accepted. This result agrees with the results of some studies which found that CBCW yielded the production of better quality texts (e.g., Abrams, 2019;Al-Shumaimeri, 2011;Arslan & Sahin-Kizil, 2010;Bailey & Judd, 2018;Beltrán, 2010;Daskalogiannaki, 2012;Dobao, 2012;Doult & Walker, 2014;Kessler & Bikowski, 2010;Mak & Coniam, 2008;McDonough & García-Fuentes, 2015;Mills & Exley, 2014;Myers, 2014;Shukor & Noordin, 2014;Strobl, 2014;Togatorop, 2015;Villarreal & Gil-Sarratea, 2019;Wichadee, 2011;Yeh, 2014;.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, this hypothesis was rejected. This result agrees with the results of other studies which found that CBCW did not lead to the production of longer texts (e.g., Elola & Oskoz, 2010;Villarreal & Gil-Sarratea, 2019) and disagrees with the results of some other studies which found that writing collaboratively makes writers produce more content (e.g., Daskalogiannaki, 2012;Doult & Walker, 2014;Mak & Coniam, 2008;Mills & Exley, 2014;Storch, 2011;. A possible explanation for this result is the small number of participants (N = 21).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In line with these findings, the evidence suggests that collaborative written tasks trigger more negotiation between learners and offer greater benefits for learning than tasks that do not require learners' composition of a text (Nassaji & Tian, 2010;Teng, 2017). When writing together, learners tend to produce more accurate compositions than they do when writing individually (Villarreal & Gil-Sarratea, 2019;Wigglesworth & Storch, 2009). Finally, the discussion and resolution of the LREs learners engage in when working together provide them with further opportunities for L2 learning (Storch, 2013).…”
Section: Writing Tasksmentioning
confidence: 67%
“…This experience resulted in learning and knowledgebuilding in idea generation, which they later applied in their individual writing. As a result, writing produced by collaborative writing is superior in terms of grammatical accuracy and linguistic complexity (Villarreal & Gil-Sarratea, 2019). In fact, according to de Oliveira & Smith (2019), when learners were assisted by a more capable partners, they were able to produce more target language.…”
Section: "My Writing Is Not Good When I Write My Homework Alone It mentioning
confidence: 99%